The Future of Programming Languages and Programmers - Fraser, Steven D.; Bak, Lars; DeLIne, Robert; Feamster, Nick; Kuper, Lindsey; Lopes, Cristina V.; Wu, Peng (SPLASH Companion 2015 Companion Proceedings of the 2015 ACM SIGPLAN International Conference on Systems, Programming, Languages and Applications: Software for Humanity, 2015)
In the beginning “programs” were patterns of bits that commanded the execution of individual machines. As machines evolved in complexity – languages evolved, starting with a variety of assembly languages and growing to encompass higher levels of abstraction. Over the years – somewhat surprisingly – programmers evolved from engineers at the pinnacle of their profession with many years of experience to individuals not yet 10 years old giving evidence that programming does not necessarily require a formal education. This panel will bring together a diverse set of industry and academic professionals to discuss the future of programming languages and programmers.